DEVELOPMENT CREATIVE CAPABILITIES OF STUDENTS BY FACILITIES of THE WATER-COLOUR PAINTING - L.A. Shcherbakova (Academy of Cognitive and Natural Sciences, 2022)
In the article methods and methods of development of creative capabilities are examined by facilities o f the water-colour painting on employments on the special course "Technology of the water-colour painting" on the artistically-graphic faculties of higher pedagogical establishments.